(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Analysis of consumer behavior is an important aspect to understand the underlying factors affecting the success of e-commerce. Such analyses help the e-businesses identify the value addition customers look for while adopting this new method of conducting business. This research study has been conducted with the objective of identifying the determinants of the online shopping experience influencing customer’s buying behaviour while purchase of electronic goods leading to the technology acceptance model adoption for determining the online shopping behaviour. The research methodology used for the research is primary data collection with the help of questionnaire and factors have been identified through factor analysis using SPSS 20. Nine hypotheses were formulated on the basis of the relationships between factors indicated in the conceptual Framework developed to indicate the B2C e-commerce experience determinants for online purchase of electronic goods. The techniques used are Exploratory and Confirmatory Factor Analysis followed by the conceptual model testing using Structural Equation Modelling technique in AMOS 22. The findings of this research study accepts the model developed to be a good fitting model with the estimate of the regression weights between all the major constructs found to be significant.